PENERAPAN METODE ROLE PLAY PADA MATAKULIAH PUBLIC SPEAKING UNTUK MAHASISWA JURUSAN PENDIDIKAN BAHASA INGGRIS DI IAIN SURAKARTA - Imroatus Solikhah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This study explores instructional process, individual performance, and attainments on public speaking. Classroom action research design with three cycles and 12 meetings was used.  Conducted in IAIN Surakarta on March to June 2016, it assigned 26 students of semester IV-B as subject. Check list, interview, and field notes were used as the instruments.  The analyses foused on classroom participation, individual performance, and scores on formative test. This study revealed that: (1) In Cycle I, motivation, partipation and  performance were low, mean scores of classrom participation was 64.10% (fair), individual performance 58.46 (low) and formative test 65.12 (fair); (2) In Cycle II, learning participation, encouragement and motivation increased. Average scores on classroom participation was 81,41% (good), individual performance 71,92% (fair) and formative test 74,81 (fair). (3) Cycle III achieved higher gains in participation, motivation, enrouragement, and test. Average scores on classroom participation, individual performance and formative test attainments were 83,98% (good), 81,54% (good), and 80,27 (good). The use of 14 aspects of public speaking as template and appeals of persuation from Aristoteles: ethos, pathos and logos was crucial.